Remnant-Preserving Anterior Cruciate Ligament Reconstruction Using a Three-Dimensional Fluoroscopic Navigation System - Taketomi, Shuji; Inui, Hiroshi; Sanada, Takaki; Nakamura, Kensuke; Yamagami, Ryota; Masuda, Hironari; Tanaka, Sakae; Nakagawa, Takumi (Knee Surgery and Related Research, 26(3), 2014)
Recently, remnant-preserving anterior cruciate ligament (ACL) reconstruction has been increasingly performed to achieve revascularization, cell proliferation, and recovery of high-quality proprioception. However, poor arthroscopic visualization makes accurate socket placement during remnant-preserving ACL reconstruction difficult. This study describes a surgical technique used to create an anatomical femoral socket with a three-dimensional (3D) fluoroscopy based navigation system during technically demanding remnant-preserving ACL reconstruction. After a reference frame was attached to the femur, an intraoperative image of the distal femur was obtained, transferred to the navigation system and reconstructed into a 3D image. A navigation computer helped the surgeon visualize the entire lateral wall of the femoral notch and lateral intercondylar ridge, even when the remnant of the ruptured ACL impeded arthroscopic visualization of the bone surface. When a guide was placed, the virtual femoral tunnel overlapped the reconstructed 3D image in real time; therefore, only minimal soft tissue debridement was required. We treated 47 patients with remnant-preserving ACL reconstruction using this system. The center of the femoral socket aperture was calculated according to the quadrant technique using 3D computed tomography imaging. The femoral socket locations were considered to be an anatomical footprint in accordance with previous cadaveric studies. The 3D fluoroscopy-based navigation can assist surgeons in creating anatomical femoral sockets during remnant-preserving ACL reconstruction.